The Effects of Calcium and Vitamin D3 in Diet on Plasma Calcium and Phosphorus, Eggshell Calcium and Phosphorus Levels of Laying Hens in Late Laying Production Period - Bolukbasi, S. Canan; Celebi, Saban; Utlu, Necati (International Journal of Poultry Science, 2005)
This experiment was carried out to investigate the effect dietary calcium level and vitamin-D3 on calcium and phosphorus concentrations in plasma and eggshell of laying hens in late production period. Two hundred forty 70 weeks white lohman LSL laying hens were randomly assigned to ten groups equally (n=24) each treatment was replicates six times. Experimental diets were prepared by adding calcium at the levels of 0, 1, 1.5, 2, and 2.5% to basal diet with and without vitamin D3 (3000 IU/kg) respectively (T1 e.t T10). All diets were isocaloric and isonitrogenous, study was lasted eight weeks. Plasma Ca and P, eggshell Ca and P concentrations were evaluated in this study. All parameters were measured these plasma Ca and P, eggshell Ca and P levels were affected from dietary treatments by statistically significant (P< 0.01). Calcium supplementation significantly (P< 0.01) increased plasma Ca level linearly, as increasing dietary Ca level. Ca supplementation also caused significant differences both Ca and P levels of eggshell and plasma P concentrations. Eggshell Ca concentration of the T5 (supplementing 1.5% Ca) was significantly greater than those fed the others diets. However the highest eggshell P level was in T7 (adding 2 % Ca), regardless of vitamin D3 in diet. As for vitamin D3 supplementation significantly (P< 0.01) increased Ca concentration both plasma and eggshell. Vitamin D3 supplementation also increased P concentration in plasma.